Pengaruh Model Pembelajaran Berbasis Masalah terhadap Kemampuan Berpikir Logis pada Peserta Didik - Muh. Hasbi Assidiq. R; Rahmawati Rahmawati; Edy Kurniawan (Simpati, 2024)
This research aims to: (1) describe how much logical thinking ability increases in students who are taught using the problem-based learning model; (2) describe how much logical thinking ability increases in students who are taught using conventional learning models; and (3) analyze the influence of the problem-based learning model on students' logical thinking abilities. The research method used was quasi-experimental with a Nonequivalent Control Group Design. Data collection techniques use logical thinking ability tests (pretest and posttest). The data analysis technique uses descriptive analysis and inferential analysis. The research results show that: (1) the logical thinking ability of students taught using the problem-based learning model has increased by 0.75 (high category) with an average pretest score of 9.40 and posttest of 26.30; (2) the logical thinking ability of students taught using conventional learning models increased by 0.22 (low category) with an average pretest score of 12.53 and posttest of 17.17; (3) there is a significant influence of the problem-based learning model on students' logical thinking abilities, which is proven by a probability value of 0.001 <significant 0.05.